Giving power to those having less power: NGOs, YouTube and virality - Avgeropoulou, Aikaterini; Melanthiou, Yioula (My University, 2021)
The aim of this paper is to examine a promising, but yet unexplored relationship between cinematography, consumer behaviour and viral marketing. The main purpose is to provide a deeper understanding of how certain practices and tools can become universal drivers of virality in the context of YouTube for application by non-governmental organisations (NGOs). In order to achieve this research goal, Netnography was utilised aiming to compare the content of two viral and two non-viral campaigns, so as to draw specific insights regarding how and if the different use of various elements such as montage and content, impact on these videos' likeability and viewing. This research suggests specific techniques for NGOs to achieve engaging content through a free social medium.
Keywords: Aesthetic appeal; Audio-visual appeal; Cinematography; Consumer behaviour; Content appeal; Netnography; NGOs; Non-governmental organisation; Viral marketing; YouTube